Types of Swine Diets - Joel Brendemuhl; Bob Myer (EDIS)
Revised! AS-44, a 5-page fact sheet by Joel Brendemuhl and Bob Myer, provides an overview of the particular nutrient requirements of various classes of swine. Published by the UF Department of Animal Science, September 2009. Reviewed August 2012.